Nanoprobes for biomedical imaging in living systems - Koo, Heebeom; Huh, Myung Sook; Ryu, Ju Hee; Lee, Dong-Eun; Sun, In-Cheol; Choi, Kuiwon; Kim, Kwangmeyung; Kwon, Ick Chan (ELSEVIER SCI LTD, 2011)
Recent progress in bio and nanotechnology enables the development of various nanoprobes for biomedical imaging. The detection and imaging of specific changes in biological microenvironments play key roles in many fields such as biological mechanism study, drug screening, diagnosis of many diseases, and monitoring of therapeutic responses. Especially to obtain fine images in living systems, there are many requirements such as stability in complex condition, efficient accumulation in target site, and high sensitivity to the target molecule. For this purpose, many researchers have developed a number of nano-size probes sensitive to the external changes which are valuable from biomedical point of view. Herein, we will review the on-going challenges of developing novel nanoprobes to detect chemical or biological changes such as enzyme, oxygen, and pH, and applying them to biomedical imaging in living systems. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: IRON-OXIDE NANOPARTICLES; PEPTIDE-BASED PROBES; INDUCIBLE FACTOR-I; TUMOR HYPOXIA; DRUG-DELIVERY; PHOTODYNAMIC THERAPY; HYDROGEN-PEROXIDE; INTRACELLULAR PH; MULTIFUNCTIONAL NANOPARTICLES; GOLD NANOPARTICLES